Electoral Systems and Territorial Representation. Issue 2 (2nd July 2016) - Golosov, Grigorii V.
Abstract : This article addresses the question of how different electoral systems translate the territorial patterns of party support in the electorate, as reflected in the notion of party system nationalisation, into the party composition of legislative assemblies. The impact of electoral rules upon territorial representation is estimated empirically. The article develops a system-level index of legislative party nationalisation and, by presenting evidence from a nearly comprehensive set of the world's electoral democracies (126 country cases), shows that in proportional representation systems, the difference between party nationalisation in the electorate and in the legislature tends to be reduced, while plurality/majority systems tend to increase the gap between party system nationalisation in the electorate and in the parliament, thus narrowing the scope of territorial representation. As a result, both main varieties of electoral rules provide for comparable levels of territorial representation, even though the involved causal mechanisms are different.